Probing Photocatalytic Nitrogen Reduction to Ammonia with Water on the Rutile TiO2 (110) Surface by First-Principles Calculations - Xie, Xiao-Ying; Xiao, Pin; Fang, Wei-Hai; Cui, Ganglong; Thiel, Walter (ACS catalysis, 2019)
Photocatalytic ammonia production from air and water under ambient conditions is ideally suited for artificial nitrogen fixation. It has been the subject of several recent experimental studies with titanium dioxide and titania-based semiconductors as catalysts. The TiO2-mediated photocatalytic NH3 production from H2O and N2 is a very complex process that is not yet well understood mechanistically, which hampers further advances. In the present work, we address the detailed mechanism of N2 reduction to NH3 driven by the photolysis of water adsorbed on the rutile TiO2 (110) surface containing oxygen vacancies, by means of reliable density functional calculations (HSE06+D3//PBE+U+D3). We show that each major step of the reaction is driven by H2O photolysis and can proceed under ambient conditions. The initial N2 adsorption, the activation of the inert NN bond, and the N–N cleavage are all efficiently promoted by TiO2 surface hydroxylation and photogenerated electrons, as well as their synergistic effects, while proton-coupled electron transfers play a decisive role in the N2 reduction to NH3. These mechanistic insights can probably guide further experimental studies of TiO2 photocatalytic nitrogen fixation and NH3 photosynthesis.